Les derniers jours de la Légion des volontaires français contre le bolchevisme: De la bataille de Bobr à la dissolution de la LVF - Bene, Krisztián (Verbum – Analecta Neolatina, 2013)
The French military collaboration is generally an unknown part of the Second World War’s history. At the same time, this phenomenon is very important for the better understanding of French history during the war period. The most important unit of this collaboration was the Légion des volontaires français contre le bolchevisme (French volunteers’ legion on the Bolshevism) established by French extreme right politicians in June 1941 in occupied Paris. This military unit is considered as the 638th infantry regiment of the German army and fought on the front before Moscow in December 1941. After the heavy casualties suffered in this battle, the regiment was reorganised and deployed in the back area on the partisans from 1942 until 1944. In the summer of 1944 the unit was withdrawing from the Soviet Union and disbanded, but their soldiers had to continue the fight in the Waffen-SS.